An equity-first policy for women police around the world: strategies for change. Issue 2 (3rd April 2023) - Garcia, Venessa; Shen, Anqi
ABSTRACT: Feminist scholars have debated the issue of integration and specialising of women in policing. Whether using a 'Western' definition of integration, gender-segregated units, or specialised policing for women, research reveals that within all nations, women experience barriers to hiring and promotion and are disadvantaged, discriminated, or marginalised, within the male dominated organisation. In this article, we argue that equity must be achieved before women police are to obtain equality in the workforce. We examine different models of gender in policing around the world including an equality model, an equity model, a hybrid model, and a cultural-specific model. Our findings suggest that no nation has made policing a gender equal institution. We have thus proposed a two-stage gender policy in line with the United Nations' Sustainable Development Goals that allows equity to come first to create an equal platform for women in policing, following which gender equality may be achievable.